Comparison between audiovisual media and simulation on the toothbrushing skills of elementary school students - Sanjaya, Azlina Nuur; Suwargiani, Anne Agustina; Wardani, Riana (Universitas Padjadjaran, 2019)
Introduction: Oral health education aims to enable an individual to maintain oral health, one of which is tooth brushing. Education media can determine its success. As the development of technology, audiovisual media is also developing. Audiovisual media are commonly used nowadays for educational purpose in many fields, and simulation media in many forms are often used for education. The purpose of this study was to compare the effectiveness of audiovisual media in the form of animated film and simulation media in the form of a dental model on toothbrushing skills. Methods: Quasi-experimental that tend to comparative analytics was conducted with the sample that was taken by purposive sampling technique. Forty students of Ciganitri 2 State Elementary School (SDN Ciganitri 2) aged 12-year old participated in this study. The students were divided into two groups; the first group received an education with an animated film, and the second group received an education with dental models. Measurement of the students’ toothbrushing skills performed with pre-test and post-test. All data calculated by independent t-test in each group. Results: The film group and the study model group intervention have equal effectiveness. The paired t-test between the two groups resulted in no significant difference between the effectiveness of audiovisual media and simulation media on the students’ toothbrushing skills. Conclusion: Audiovisual media and simulation media group intervention effectively improve toothbrushing skills.Keywords: Audiovisual media, simulation media, toothbrushing skill.